Development of Electoral Law in Kazakhstan in the Context of International Standards: Problems and Prospects - BOZHKARAULY, Altai; KUBEYEV, Yerkin; KOZHAKHMETOV, Galym; MUSILIMOVA, Karlygash; YERZHANOVA, Farida; TURLAYEV, Andrey (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018, 2018)
The article reveals the results of the research on the topic ‘Constitutional and legal problems of compliance with international electoral standards in national law’. Critical remarks and recommendations of international observers are analyzed, problems of improvement of legal norms in the field of electoral law in Kazakhstan legislation are considered. The problems of legal consolidation of electoral rights of citizens, as well as the main directions of development of these rights in accordance with international standards are considered.